Analysis of the Influence of Effort Expectancy, Perceived Usefulness, and Digital Literacy on Intention to Use Retail Shopping Applications - Yanti, Jumianis; Sari, Titis Nistia; Lesmini, Lis; Robo, Salahudin; Saleh, Sahlan M.; Nugraha, Jefri Putri (Yayasan Gema Bina Nusantara, 2025)
The digital transformation in the retail sector has led to the emergence of various online shopping applications that facilitate consumer transactions. However, the successful adoption of these applications is highly influenced by user perceptions. This study aims to analyze the impact of effort expectancy, perceived usefulness, and digital literacy on the intention to use retail shopping applications. Using a quantitative approach with a survey method, data were collected from 200 respondents who are users of shopping applications in urban areas. The analysis technique used was multiple linear regression. The results indicate that all three independent variables significantly affect the intention to use. Effort expectancy has a positive effect, meaning that the easier the application is to use, the higher the user's intention to use it. Perceived usefulness also shows a strong impact, indicating that perceptions of the application's benefits play a crucial role in shaping the intention to use. Additionally, digital literacy proves to be an important supporting factor that enables users to understand and maximize the application's features optimally. This study provides contributions to application developers and retail industry players in formulating digital marketing strategies and enhancing user experience.